Digital finance and banking stability: balancing inclusion and risk in Asian economies - Muhammad Iatzaz Ul Hassan,; Wu, Mengyun; Kashif, Umair; Rasool, Yasir; Sohu, Jan Muhammad; Akhtar, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the relationship between digital financial inclusion (DFI), the digital economy (DE), and bank stability across 33 Asian economies from 2010 to 2022. Using Z-score (ZS) and Non-Performing Loans (NPLs) as measures of stability, the analysis employs Generalized Method of Moments (GMM), Generalized Least Squares (GLS), and Panel-Corrected Standard Error (PCSE) models. The findings show that DFI negatively impacts ZS and increases NPLs, indicating higher risks associated with financial inclusion. Conversely, DE positively affects ZS, enhancing bank stability, although its effect on NPLs is minimal. These results highlight the double-edged nature of DFI and the stabilizing role of DE in the banking sector. Policymakers must balance efforts to promote DFI with measures to manage associated risks, such as improving credit assessment tools and strengthening digital infrastructure. This study contributes to understanding the dynamics of digital financial transformation and its implications for banking risk in developing economies.